ANALISIS USAHA – USAHA PEMASARAN DAN PENGARUHNYA TERHADAP VOLUME PENJUALAN PRODUK BATU ALAM (KASUS USAHA DAGANG BATU ALAM KOTA PEKANBARU) - Muslia, Arini Muslia; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study aimed to : (a) evaluate the bussiness marketting and sales volume effect on Natural Stones Product, and (b) evaluate the constraints on marketting the natural stones Product. The study used qualitative and describtive approach, till no requirement on hypothesis testing. Data collecting was conducted by proposing the quesioner, interview, and observation to bussinessmen of the natural stones product of Pekanbaru. The result, concluded the busssiness marketting on sales natural stones product are giving the best services to the consumen and providing the discount to take a interest of consumen to increase the sales volume.Keyword : Bussiness marketting, Natural stone product, Sales volume.